2020
DOI: 10.1063/5.0013349
|View full text |Cite
|
Sign up to set email alerts
|

Global gyrokinetic nonlinear simulations of kinetic infernal modes in reversed shear tokamaks

Abstract: Nonlinear evolution of the kinetic ballooning mode (KBM) is investigated by extending the global toroidal gyrokinetic simulation code (GKNET) to an electromagnetic regime. It is found that the saturation process of KBM, which is unstable at high normalized pressure b, is significantly different from the ion temperature gradient (ITG) mode, which is unstable at low b. The KBMs get saturated by producing zonal flows and zonal magnetic fields. The production of zonal flow is weak in the initial saturation phase o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…It is found that the stable local maximum of E r is formed near the q min surface only in the kinetic electron cases (b) and (c). This is because the kinetic electron dynamics provide a finite phase difference between density perturbation and electrostatic potential, leading to a more unstable infernal type of linear ITG instability near the q min and resultant stronger zonal flow generation [28]. From some linear and nonlinear benchmark tests, it is confirmed that the linear growth rate in the hybrid electron case is roughly 1.7 times larger than that in the adiabatic electron case and the established zonal flow is corrugated, leading to the nonlinear upshift of critical ITG (∼ 10%).…”
Section: Spontaneous Itb Formation In Reversed Magnetic Shear Plasmamentioning
confidence: 99%
“…It is found that the stable local maximum of E r is formed near the q min surface only in the kinetic electron cases (b) and (c). This is because the kinetic electron dynamics provide a finite phase difference between density perturbation and electrostatic potential, leading to a more unstable infernal type of linear ITG instability near the q min and resultant stronger zonal flow generation [28]. From some linear and nonlinear benchmark tests, it is confirmed that the linear growth rate in the hybrid electron case is roughly 1.7 times larger than that in the adiabatic electron case and the established zonal flow is corrugated, leading to the nonlinear upshift of critical ITG (∼ 10%).…”
Section: Spontaneous Itb Formation In Reversed Magnetic Shear Plasmamentioning
confidence: 99%
“…The global effect is found to be a key to resolve the problem, and leads to a quasi-steady turbulent state [37][38][39][40][41][42]. In addition, global simulations enable us to evaluate turbulent transport in zero magnetic shear region which can appear in plasmas with weak or reversed magnetic shear [43,44], from which internal transport barrier is initiated in higher input power regime [45].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the fluid models, kinetic models have also been used for the analysis of the infernal modes. The linear stability analysis [15] and the nonlinear simulation analysis [16] of kinetic infernal modes in circular cross-section tokamaks have been performed using a gyrokinetic model.…”
Section: Introductionmentioning
confidence: 99%
“…Figure16. The radial profile of the (m, n) = (0, 0) component of the pressure at the initial state (the black curve) and at the saturated state (the green and red curves) corresponding to figure 14.…”
mentioning
confidence: 99%